DESIGN OF TRAINING ON THE BASIS OF A PACKAGE OF PRACTICAL PROGRAMS FOR THE EFFECTIVE ORGANIZATION OF THE CALCULATION OF PROBLEMS RELATING TO THE APPLICATIONS OF THE DEFINITE INTEGRAL (Web of Technology: Multidimensional Research Journal, 2024)
In the article is a package of practical programs. It refers to a set of interconnected programs for solving specific class problems.